Dependent Controllers and Regulation Policies: Theory and Evidence - Carmine Guerriero (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper analyzes the effects of supervisors (i.e., regulators and judges) selection rules on regulated prices. A checks and balances regulatory review process strengthens the role of the judicial power and election increases the populism of implicitly motivated supervisors. Election arises when the risk related to expropriation of sunk investments and the inter-party distance are lower. Employing U.S. electric power markets data, the empirical evidence strongly confirms these predictions. Indeed, when treated as endogenous, only the election of administrative law judges and not the one of regulators significantly lowers the level of electricity rates. Moreover a more effective supervision technology shows a marginal negative effect on regulated rates as well.
Keywords: K23; L51; Q43; 330; Election; Agency; Judges; Regulation; Electricity; Regulierung; Staatliche Preispolitik; Elektrizitätswirtschaft; Theorie; USA